Treatment decisions for patients with peripheral artery disease and symptoms of claudication: Development process and alpha testing of the SHOW-ME PAD decision aid. (June 2021) - Smolderen, Kim G; Pacheco, Christina; Provance, Jeremy; Stone, Nancy; Fuss, Christine; Decker, Carole; Bunte, Matthew; Jelani, Qurat-ul-ain; Safley, David M; Secemsky, Eric; Sepucha, Karen R; Spatz, Erica S; et al.
Patients with peripheral artery disease (PAD) face a range of treatment options to improve survival and quality of life. An evidence-based shared decision-making tool (brochure, website, and recorded patient vignettes) for patients with new or worsening claudication symptoms was created using mixed methods and following the International Patient Decision Aids Standards (IPDAS) criteria. We reviewed literature and collected qualitative input from patients ( n = 28) and clinicians ( n = 34) to identify decisional needs, barriers, outcomes, knowledge, and preferences related to claudication treatment, along with input on implementation logistics from 59 patients and 27 clinicians. A prototype decision aid was developed and tested through a survey administered to 20 patients with PAD and 23 clinicians. Patients identified invasive treatment options (endovascular or surgical revascularization), non-invasive treatments (supervised exercise therapy, claudication medications), and combinations of these as key decisions. A total of 65% of clinicians thought the brochure would be useful for medical decision-making, an additional 30% with suggested improvements. For patients, those percentages were 75% and 25%, respectively. For the website, 76.5% of clinicians and 85.7% of patients thought it would be useful; an additional 17.6% of clinicians and 14.3% of patients thought it would be useful, with improvements. Suggestions were incorporated in the final version. The first prototype was well-received among patients and clinicians. The next step is to implement the tool in a PAD specialty care setting to evaluate its impact on patient knowledge, engagement, and decisional quality.ClinicalTrials.gov Identifier: NCT03190382